Analisis Efektivitas Pengawasan Pengelolaan Tempat Pelelangan Ikan (TPI) Arumbai Oleh Dinas Perikanan Kota Ambon - Sulfa Dewianti; Mohamad Arsad Rahawarin; Stanislaus K. Ohoiwutun (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This research is a descriptive qualitative research. It aims to analyze the effectiveness of supervision of the management of the Arumbai Fish Landing Place by the Ambon City Fisheries Service.This research was conducted at Arumbai Fish Auction Place. Primary data collection is conducted through interviews with a number of informants who are considered to have insight and knowledge, which is complete regarding data and information related to the problems encountered in the study so as to be able to provide precise and accurate information during the research process.The results showed that the effectiveness of supervision of the management of the Arumbai Fish Auction Place has not been running optimally and needs to be improved to support the effectiveness of the Fish Auction Place so that it can run in accordance with its functions and objectives. This can be seen from the indicators of the supervision process based on the place of implementation. These indicators are then influenced by supporting factors and inhibiting factors that affect the effectiveness of supervision of the management of the Arumbai Fish Auction Site by the Ambon City Fisheries Service.